Effects of Moina micrura (Kurz) from two different culture sources as a replacement of Artemia spp. in production of Macrobrachium rosenbergii (de Man) post‐larvae - ALAM, M.J.; ANG, K.J.; CHEAH, S.H.; AMBAK, M.A.; SAAD, C.R. (Hindawi Limited, 1993)
Abstract. The effects of Artemia spp. and of Moina micrura from two culture sources, poultry manure and Chlorella supplemented with baker's yeast, on production of Macrobrachium rosenbergii (de Man) post‐larvae (PL) were evaluated. Significantly higher production of 18·13 ± 1·45 PL/I was obtained for the larvae fed with 50:50 mixture of Artemia and Moina cultured on poultry manure compared to that for larvae fed Artemia alone (14·27 ± 1·64PL/I). Regardless of the culture source, the post‐larval production was the lowest (9·23 ± 1·22 and 11·26 ± 1·33 PL/I for the larvae fed Moina. The higher dietary value of Moina cultured on poultry manure was related to the high content of n–3 HUFA particularly 20:5n‐3 compared to Artemia and Moina cultured on Chlorella and yeast.